2015
DOI: 10.1136/neurintsurg-2015-011861
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy with the Trevo ProVue device in ischemic stroke patients: does improved visibility translate into a clinical benefit?

Abstract: Neurothrombectomy with TPV is feasible, effective, and safe. The recanalization rate compares favorably with reported data in the literature. Improved structural radiopacity may facilitate neurothrombectomy or influence the course of action during retrieval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…Our overall favorable outcome rate (35.3%) is comparable to that of MR CLEAN (32.6%), which can be explained by similar inclusion criteria, periprocedural timings, and the IVT rate [18]. The same holds good in comparison to large case series or registries with favorable outcomes up to 70% [2,3,13,24,26,30,35]. Our rate of concomitant IVT was in line with published registry data and not significantly different between ILVO and CLVO groups [36].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our overall favorable outcome rate (35.3%) is comparable to that of MR CLEAN (32.6%), which can be explained by similar inclusion criteria, periprocedural timings, and the IVT rate [18]. The same holds good in comparison to large case series or registries with favorable outcomes up to 70% [2,3,13,24,26,30,35]. Our rate of concomitant IVT was in line with published registry data and not significantly different between ILVO and CLVO groups [36].…”
Section: Discussionsupporting
confidence: 59%
“…In our study, the overall rate of successful reperfusion (79.9%) is within the range of core-lab controlled results (58.7-88%) [18,19,20,21,22], yet lower than that in self-reported series with reperfusion rates up to 91% [2,3,13,15,16,24,25,26,27]. One putative explanation might be the blinded regrading of all digital subtraction angiography images according to the Cerebral Angiographic Revascularization Grading standards, thereby ensuring common operator-independent grading standards over time.…”
Section: Discussionmentioning
confidence: 88%
“…Our revascularization (TICI≥2b) rate of 88% is comparable to results obtained by recent large randomized studies that reported revascularization rates of 56–88% in comparable occlusion sites with various stent retrievers 6–10. For the cases in which the Trevo was the only device used, our revascularization rates of 95% (TICI≥2a) and 90% (TICI≥2b) are comparable to the 91% (TICI≥2b) indicated by Kabbasch et al 11 in their analysis of 76 patients, and also comparable to the 88% (TICI≥2a) indicated by Nogueira et al 5 in the TREVO 2 study.…”
Section: Discussionsupporting
confidence: 85%
“…Full structural visibility of the stent during deployment and retrieval allow procedural adaptation or modification by enhancing the operator's understanding of the actual stent-clot or stent-vessel interaction (16). Subjectively, proper visualization of the stent helped to position the TV stentriever in the correct position at emergency situations where the patient was not cooperative.…”
Section: Discussionmentioning
confidence: 99%
“…The TV was designed to facilitate proper visualization of the complete device by integrating the platinum wires into the stent struts itself (16)(17)(18). Full structural visibility of the stent during deployment and retrieval allow procedural adaptation or modification by enhancing the operator's understanding of the actual stent-clot or stent-vessel interaction (16).…”
Section: Discussionmentioning
confidence: 99%